Study of concrete mix by adding Dolomite in conventional concrete as partial replacement with cement. (2023) - Gusain, Ishita; Sharma, Saurav; Debarma, Samrat; Kumar Sharma, Amit; Mishra, Nitin; Prakashrao Dahale, Prasad
Abstract: Massive quantities of dolomite wastes are produced every year in under-developing nations like India. Disposal of dolomite waste is a very severe problem as it requires huge space for its disposal and very small quantity of waste is recycled or reused. This experimental study has been carried out to assess the effect of partial replacement of coarse aggregate by dolomite waste on workability, compressive strength and flexural strength of concrete. In this paper by using waste dolomite in concrete as partial replacement in various percentages with coarse aggregate. For making M25 grade using IS: 10262–2019. Objective of study to analyzing physical property of fresh concrete that is workability & compressive strength, flexural strength of hard concrete in M25 by adding dolomite as partial replacement in conventional concrete mix with 5%, 10%, 15%, 20%, 25%, and 30% The cube samples of M25 grade concrete mix are cast for study purpose. The important aim of this paper is to utilize the dolomite waste in concrete and to make the construction ecofriendly and to make concrete work economic to some extent. It is also essential to protect the natural raw resources like stone aggregates, sand etc. Therefore, the sustainable concept was introduced in modern construction industry.